Pengaruh Ukuran Perusahaan, Leverage, dan Profitabilitas terhadap Tax Avoidance pada Perusahaan Sub Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2019–2023 - Nova Khabibatul Mardliyah; Rita Andini; Utami Puji Lestari (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the factors that affect tax avoidance in mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. The main focus of this study is to determine the influence of company size, leverage, and profitability on the level of tax avoidance carried out by the company. The research population includes all mining sub-sector companies listed on the IDX, while the sample is selected based on certain criteria relevant to the research objectives. The analysis method used is Multiple Linear Regression Analysis with the help of SPSS software version 23 to test the relationship between independent and dependent variables. The results of the study show that company size has a positive effect on tax avoidance, leverage does not have a significant effect on tax avoidance, while profitability has a negative effect on tax avoidance. These findings provide important implications for corporate management and policymakers in understanding the factors that drive tax avoidance practices in the mining sector, as well as a reference for future research in efforts to optimize tax policies in Indonesia.